Effects of melatonin applications on Anatolian black pine (Pinus nigra J. F. Arnold. subsp. pallasiana (Lamb.) Holmboe) afforestation performance in semi-arid areas - Yer Çelik, Esra Nurten; Ayan, Sezgin; Özel, Halil Barış; Turfan, Nezahat; Yer, Batın Mehmet; Abdaloğlu, Gülbahar (BioResources, 2023)
Melatonin, a substantial hormone, is a natural antioxidant agent that functions as a protector against the harmful effects of free radicals. Studies have found that “exogenous melatonin” applications have a positive effect on the growth and development of plants. This study investigated the adaptation of the seedlings that were transported from the nursery to the afforestation site for the process of planting. In 2019 the 2+0 aged bare-rooted Kastamonu/Taşköprü Anatolian Black pine seedlings, which are suitable for planting in semi-arid areas, were selected as research materials. Four different doses of “exogenous melatonin” (250, 500, 1000, and 1500 μM) were administered through two different methods (root-dipping and needle-spraying). Morphological seedling characteristics and bioactive chemical variables were measured for the control group and the seedlings treated with different doses of melatonin. Antioxidant enzyme activities were identified. When both the needle-spraying and root-dipping methods for melatonin application were evaluated in terms of morphological and biochemical variables, the best results were determined in low doses (250 to 500 μM). The results suggest that melatonin provides support to the metabolic process for the resistance of seedlings to low temperatures and semi-arid climatic conditions.
Keywords: pallasiana; Pinus Nigra Subsp. Pallasiana; Hydrogen-Peroxide; Field Performance; exogenous melatonin; Needle; Temperate Forest; pinus nigra subsp. pallasiana; root-dipping; Needle-Spraying; Root-Dipping; Carbohydrate Reserves; reactive oxygen species; Pinus nigra subsp; Exogenous Melatonin; Seasonal-Changes; Water-Deficit; Plants; Root -dipping; needle-spraying; Oxidative Stress; spraying; Seedlings; Reactive Oxygen Species; Reactive oxygen species; Exogenous melatonin; Antioxidant Systems; TP248.13-248.65; Biotechnology; 2. Zero hunger; 15. Life on land